2016
DOI: 10.1007/s13105-016-0479-3
|View full text |Cite
|
Sign up to set email alerts
|

Kaempferol inhibits the production of ROS to modulate OPN–αvβ3 integrin pathway in HUVECs

Abstract: In the present study, we tested the hypothesis that aldosterone regulates osteopontin (OPN)-related signaling pathways to promote nuclear factor κB (NF-κB) activation in primary human umbilical vein endothelial cells (HUVECs) and that kaempferol, a flavonoid compound, blocks those changes. Aldosterone induced productions of reactive oxygen species (ROS), OPN, interleukin-6 (IL-6), and tumor necrosis factor alpha (TNF-α) and expression of nicotinamide adenine dinucleotide phosphate-oxidase 4 (Nox4), NF-κB, OPN,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…Regulation of osteopontin (OPN)‐related signaling pathways is linked with aldosterone hormone by promoting activation of NF‐κB in primary human umbilical vein endothelial cells (HUVECs). On the other hand, kaempferol was found to lower production of ROS, TNF‐α, OPN, NF‐κB, inhibitor of NF‐κB alpha phosphorylation (P‐IκBα), IL‐6, and reduced nicotinamide adenine dinucleotide phosphate‐oxidase 4 (Nox4), αvβ3 integrin, and P‐IκBα expressions (Xiao, Lu, Liu, & Luo, ). In a similar fashion, Zhou et al () showed that kaempferol prevents myocardial I/R injury in rats by decreasing the levels of TUNEL‐positive cell rate and by reducing myocardial infarct size.…”
Section: Health Perspectivesmentioning
confidence: 99%
“…Regulation of osteopontin (OPN)‐related signaling pathways is linked with aldosterone hormone by promoting activation of NF‐κB in primary human umbilical vein endothelial cells (HUVECs). On the other hand, kaempferol was found to lower production of ROS, TNF‐α, OPN, NF‐κB, inhibitor of NF‐κB alpha phosphorylation (P‐IκBα), IL‐6, and reduced nicotinamide adenine dinucleotide phosphate‐oxidase 4 (Nox4), αvβ3 integrin, and P‐IκBα expressions (Xiao, Lu, Liu, & Luo, ). In a similar fashion, Zhou et al () showed that kaempferol prevents myocardial I/R injury in rats by decreasing the levels of TUNEL‐positive cell rate and by reducing myocardial infarct size.…”
Section: Health Perspectivesmentioning
confidence: 99%
“…Since SP was administered for up to 5 consecutive days in vivo , it is possible that several tissues involved in a wound healing process could be affected. For instance, SP can reduce inflammation in the endothelium and vascular smooth muscle cells, 50–52 regulate other immune cells, such as T reg cells, T H 17 helper cells, and glial cells 53,54 . In addition, SP inhibited fibrosis in cardiac and kidney injury 55,56 .…”
Section: Discussionmentioning
confidence: 99%
“…Aldosterone also impacts ECs and may dimish endothelial function via the mineralocorticoid receptor (MR) by increasing NOX expression independent of blood pressure [118]. Preliminary evidence suggests that polyphenols, such as kaempferol, may also inhibit MR in human umbilical vein endothelial cells (HUVECs), resulting in the reduction of ROS and inflammatory signaling [119,120]. Thus, berries may target RAAS primarily via reduced ACE activity and decreased AT 1 R but may also inhibit the production and action of aldosterone.…”
Section: Regulation Of Raas By Berry Polyphenolsmentioning
confidence: 99%
“…Aldosterone ↓ [116,117,119,120] Caffeic acid, quercetin and kaempferol May decrease the synthesis of aldosterone in the adrenal cortex and decrease the action of aldosterone in the kidneys, resulting in reduced blood pressure, decreasing microcirculatory resistance. Additionally, polyphenols may decrease MR activity in the endothelium, resulting in reduced endothelial dysfunction.…”
Section: Gallic Acid and Blueberriesmentioning
confidence: 99%